The E3 ubiquitin ligase EDD is an adverse prognostic factor for serous epithelial ovarian cancer and modulates cisplatin resistance in vitro - O'Brien, P M (Nature Publishing Group, 2008)
Despite a high initial response rate to first-line platinum/paclitaxel chemotherapy, most women with epithelial ovarian cancer relapse with recurrent disease that becomes refractory to further cytotoxic treatment. We have previously shown that the E3 ubiquitin ligase, EDD, a regulator of DNA damage responses, is amplified and overexpressed in serous ovarian carcinoma. Given that DNA damage pathways are linked to platinum resistance, the aim of this study was to determine if EDD expression was associated with disease recurrence and platinum sensitivity in serous ovarian cancer. High nuclear EDD expression, as determined by immunohistochemistry in a cohort of 151 women with serous ovarian carcinoma, was associated with an approximately two-fold increased risk of disease recurrence and death in patients who initially responded to first-line chemotherapy, independently of disease stage and suboptimal debulking. Although EDD expression was not directly correlated with relative cisplatin sensitivity of ovarian cancer cell lines, sensitivity to cisplatin was partially restored in platinum-resistant A2780-cp70 ovarian cancer cells following siRNA-mediated knockdown of EDD expression. These results identify EDD as a new independent prognostic marker for outcome in serous ovarian cancer, and suggest that pathways involving EDD, including DNA damage responses, may represent new therapeutic targets for chemoresistant ovarian cancer.